Unraveling the pathogenesis of bone marrow hematopoietic injury and the therapeutic potential of natural products - Jing Long; Hengzhou Lai; Yuqing Huang; Fengming You; Yifang Jiang; Qixuan Kuang (Pharmacological Research)
Bone marrow hematopoietic injury encompasses a range of pathological conditions that disrupt the normal function of the hematopoietic system, primarily through the impaired production and differentiation of bone marrow hematopoietic cells. Key pathogenic mechanisms include aging, radiation damage, chemical induction, infection and inflammation, and cross-talk with non-hematopoietic diseases. These pathological factors often lead to myelosuppression and myeloid skewing. Furthermore, we explored the potential and application prospects of natural products in the treatment of bone marrow hematopoietic injury. Natural products, particularly those derived from Chinese herbal medicines and other natural sources, have emerged as promising therapeutic options due to their distinctive mechanisms and minimal side effects. A deeper understanding of the underlying mechanisms of bone marrow hematopoietic injury could illuminate how natural products exert their effects, thereby optimizing treatment strategies and offering safer, more effective options for patients. Future research should leverage emerging technologies to further elucidate the composition and interactions within the bone marrow microenvironment, as well as the specific pathways through which natural products modulate hematopoietic dysfunction.